Given that lim*x*→−1*f*(*x*)=5 and lim*x*→−1*g*(*x*)=−1, evaluate the following.

lim*x*→−1(*f*(*x*)⋅*g*(*x*))

(If the limit does not exist, enter ∅.)

Given that lim*x*→−1*f*(*x*)=5 and lim*x*→−1*g*(*x*)=−1, evaluate the following.

lim*x*→−1(*f*(*x*)⋅*g*(*x*))

(If the limit does not exist, enter ∅.)

lim x→-1 f(x)g(x)=(5)(-1)=-5, product of the limits

Example: f(x)=(x²+7x+6)/(1+x), g(x)=(x²+x)/(1+x); so f(x)g(x)=(x⁴+8x³+13x²+6x)/(1+x)².

lim x→-1 f(x) = 5 and lim x→-1 g(x) = -1 (because denominator is a factor of the numerator)

lim x➝-1 (x⁴+8x³+13x²+6x)/(1+x)²=-5, because denominator is a factor of the numerator and f(x)g(x) reduces to x²+6x (for x≠-1), which has the value -5 when x=-1.

- All categories
- Pre-Algebra Answers 12.3k
- Algebra 1 Answers 25.3k
- Algebra 2 Answers 10.5k
- Geometry Answers 5.2k
- Trigonometry Answers 2.6k
- Calculus Answers 6.1k
- Statistics Answers 3k
- Word Problem Answers 10.2k
- Other Math Topics 6.7k

81,947 questions

86,330 answers

2,238 comments

71,541 users